2017
DOI: 10.3389/fmicb.2017.00503
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas Diversity and Antimicrobial Susceptibility in Freshwater—An Attempt to Set Generic Epidemiological Cut-Off Values

Abstract: The importance of the role of environment in the dissemination of antimicrobial resistant bacteria is now well recognized. Thus, bacterial indicators to monitor the phenomena are required. The Aeromonas genus is autochthonous in the aquatic environment and easy to detect in any water type, such as freshwater, or wastewater. These microorganisms are also causing infections in humans and animals (including fish). Furthermore, as Aeromonas spp. is able to acquire antimicrobial resistance mechanisms, it is candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 37 publications
(58 reference statements)
9
76
3
1
Order By: Relevance
“…The bacteria were isolated from common environments and are therefore likely to be exposed to similar antibiotic resistance selection pressure. Besides, this finding may be in support of previous reports that genus Aeromonas is an indicator bacterium for antimicrobial resistance in the aquatic ecosystem (Baron et al 2017;Penders and Stobberingh 2008;Usui et al 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The bacteria were isolated from common environments and are therefore likely to be exposed to similar antibiotic resistance selection pressure. Besides, this finding may be in support of previous reports that genus Aeromonas is an indicator bacterium for antimicrobial resistance in the aquatic ecosystem (Baron et al 2017;Penders and Stobberingh 2008;Usui et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Two genera were tested: genus Aeromonas, due to its high pathogenicity in fish and high prevalence in the study area. It has also been used as an indicator bacterium for antibiotic susceptibility in aquatic environments (Baron et al 2017;Penders and Stobberingh 2008;Usui et al 2016); and Genus Plesiomonas due to its high prevalence in the study area, it was considered to represent family Enterobacteriaceae, a group to which many fish bacteria belongs. A total of 155 isolates (Aeromonas spp.…”
Section: Determination Of Antibiotic Susceptibility Of Selected Bacteriamentioning
confidence: 99%
“…The extensive use and misuse of antimicrobial agents in hospitals and in fish farming and the consequent selective pressure lead to the development of antibiotic resistance; which has become a serious global problem (Akova, 2016;Dubert et al, 2016;Baron et al, 2017). It is well documented that both clinical and environmental bacterial pathogens may harbour severe antibiotic resistance traits that lead to challenges in treating patients with existing antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…For the two antimicrobials, in the present studies very little information of that kind is available. Among environmental A. sobria the wild‐type cut‐off was 0.016/0.031 . The enrofloxacin MIC values of the strains tested were 0.03, 0.015, 0.008, 0.03 and 0.015 mg/L for A. sobria , and 0.004, 0.06, 0.008, 0.004 and 0.004 mg/L for V. anguillarum .…”
Section: Resultsmentioning
confidence: 97%
“…In studies of environmental Aeromonas spp. , Baron et al found a provisional cut‐off value (CO WT ) for A. sobria of 0.06/0.03 mg/L . Transforming the 0.03 mg/L CO WT level to inhibition zone diameter values and comparing it with an MIC level of 0.5 mg/L the resulting curves are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%